Immunological Changes During Space Travel: A Ground-Based Evaluation of the Impact of Neutron Dose Rate on Plasma Cytokine Levels in Human Whole Blood Cultures - Fisher, Randall; Baselet, Bjorn; Vermeesen, Randy; Moreels, Marjan; Baatout, Sarah; Rahiman, Farzana; Miles, Xanthene; Nair, Shankari; du Plessis, Peter; Engelbrecht, Monique; Ndimba, Roya J.; Bolcaen, Julie; et al. (Frontiers in Physics, 2020)
A better understanding of the combined impact of different space stressors on human health is urgently warranted, considering the upcoming long-duration missions beyond lower Earth orbit. Therefore, a growing number of particle accelerator facilities implement ground-based set-ups to study the effect of simulated space radiation with simulated psychological or physical stressors. The immune system is highly sensitive to these types of stressors and limited information is currently available on the impact of the complex space radiation environment on the astronauts’ immune function. This pilot study presents a first step in the implementation of a ground-based set-up with neutron irradiation, which is considered to be an important secondary component in space radiation fields. The effect of dose rate on immune alterations was studied using the in vitro cytokine release assay. Whole blood samples (n=8) were exposed to 0.125 or 1Gy of neutron irradiation (fluence-weighted average energy: 29.8 MeV) at a lower dose rate (LDR) of 0.015Gy/min and a higher dose rate (HDR) of 0.400Gy/min. Immediately post-irradiation, blood samples were stimulated with lipopolysaccharide (LPS), heat-killed Listeria monocytogenes (HKLM) or lectin pokeweed mitogen (PWM), and incubated for 24 hours. Cell-mediated immunity was examined by analysing interleukin-2 (IL-2), interferon-gamma (IFN-γ), tumour necrosis factor-alpha (TNF-α), and interleukin-10 (IL-10) plasma levels. Stimulants significantly increased all cytokine levels except IL-2, where only PWM induced a significant increase. In general, no statically significant changes were observed in IL-2, IFN-γ and TNF-α concentrations at different neutron doses and dose rates when compared to their stimulated, sham-irradiated controls. After PWM-stimulation, IL-10 levels were significantly increased at 0.125Gy HDR and 1Gy LDR. In a pooled analysis, the HDR significantly increased IL-2 titres (under PWM-stimulation) and IFN-γ titres (with all stimulants), but significantly decreased TNF-α secretion in unstimulated cultures. Due to the limited sample number, no strong conclusions could be made in this pilot study on the effect of neutron radiation as a single stressor on cytokine secretion in response to different stimuli. However, some interesting trends and dose rate effects were observed, which pave the way for future investigations on the synergistic effects of multiple space stressors on immune cell function.